Evaluating the relationship between familial poverty, Helicobacter pylori seropositivity, and all-cause mortality in the general US population - Chenyu Jiang; Luqi Zhu; Wenyuan Yang; Zhenjun Yu; Weiwei Yang; Xiaolong Jin; Yaojian Shao (Frontiers in Public Health)
PurposeSocioeconomic inequality is closely related to the incidence of Helicobacter pylori (H. pylori) infection and mortality outcomes. Accordingly, this study was designed with the goal of exploring the relationship between familial poverty, H. pylori seropositivity, and all-cause mortality among adults in the United States.MethodsData from National Health and Nutrition Examination Survey (1999–2000) was used to conduct analysis. Family poverty to income ratio (PIR) was applied to evaluate socioeconomic status. The interplay between H. pylori serostatus and PIR was evaluated through univariate and multivariable approaches. The relationship between PIR, H. pylori serostatus, and the incidence of all-cause mortality was further assessed through Cox regression analysis, restricted cubic spline, and survival analysis.ResultsA total of 3,573 individuals were included in this study. PIR values were found to be negatively associated with H. pylori seropositivity incidence after adjusting for potential covariates. Smooth curve fitting suggested that the relationship between these two variables was largely linear. Subgroup analyses confirmed that PIR values were still closely associated with H. pylori seropositivity independently. Moreover, multivariate Cox regression analysis demonstrated that lower PIR was associated with an increase in all-cause mortality in both H. pylori seropositivity and seronegative group, whereas H. pylori serostatus showed no association with all-cause mortality. Additional analysis using smooth curve fitting indicated a nonlinear relationship between PIR and all-cause mortality. The survival analysis further indicated that individuals with higher PIR values exhibited lower mortality rates, regardless of H. pylori serostatus.ConclusionThe present analyses reveal an inverse association between PIR values and H. pylori seropositivity and all-cause mortality. The relationship between PIR and all-cause mortality was not affected by H. pylori seropositivity. H. pylori serostatus is not a major risk factor for all-cause mortality. However, additional studies will be essential to better clarify the clinical relevance of these findings and to elucidate the underlying findings.